Preliminary ERP evidence of the impact of loneliness on Stroop interference for socio-emotional stimuli - Arioli, Maria; Maiocchi, Carlotta; Cattaneo, Zaira; Gianelli, Claudia; Canessa, Nicola (Frontiers in Neuroscience, 2025)
Growing evidence highlights the adverse clinical effects and societal implications of loneliness, i.e., the negative feeling associated with a perceived discrepancy between desired and existing social connections. To further understand the implicit attentional and cognitive control processes associated with loneliness, we used electroencephalography (EEG) and event-related potentials (ERPs) to investigate the relationship between loneliness levels and brain activity underlying attentional capture in a socio-emotional Stroop task. In keeping with previous reports of three-stage processing of socio-emotional words, positive–negative valence and social-individual content of word stimuli were reflected in the amplitude of ERP components associated with high-order perceptual processing and preliminary emotional decoding (P200), emotional and semantic processing (P300), and interference suppression (N450). In the later stage, the differential N450 amplitude associated with processing socially negative compared with control-neutral stimuli was negatively correlated with self-perceived loneliness levels. This finding suggests that social negative and neutral stimuli are processed more dissimilarly at higher levels of self-perceived loneliness, possibly due to increased hypervigilance toward negative social cues, like those associated with rejection or exclusion. By elucidating the neural mechanisms underlying the effects of loneliness on socio-cognitive processing, these findings provide novel insights that can guide future research and inform the development of innovative therapeutic interventions that target the consequences of perceived social disconnection.